Juri Desain Poster dan Fotografi Dalam Rangka Perayaan Mid Auntumn Festival - Evelyn Wijaya; Johan Johan; Teddy Chandra; Stefani Chandra; Martha Martha (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity was organized by Permatadhis Pelita Indonesia in order to celebrate the moon cake festival or better known as the mid autumn festival, with the theme "Spreading Love Underneath the Moonlight". The purpose of this activity is to develop creativity and skills in non-academic fields for college student of the Pelita Indonesia Institute of Business and Technology. The competition method is that participant doing register and collect posters or photographic creations via googleform link that has been provided and will be assessed by a team of judges. The elements of the poster competition assessment include creativity, caption, color composition and the message conveyed in the creation. Meanwhile, the elements of the assessment of the photography competition include conformity to the theme, creativity, captions, moments and taking photos.